A biophysical suitability model to identify best areas for the cultivation of potential cash crops: The case of basil in Valle del Cauca - Esponda Bernal, Maria Del Mar; Echeverri-Sanchez, Andrés Fernando; Aguirre-Gonzalez, Eduar Fernando; Andrade, Robert Santiago (Elsevier, 2024)
CONTEXT Basil (Ocimum basilicum L.) cultivation in Colombia has increased exponentially since 2006 (over 41-fold in relation to 2020), driven by a favorable export market. It is a particularly promising crop for creating livelihood opportunities in the region, especially for vulnerable populations such as victims of forced displacement and single mothers. Basil cultivation can foster economic empowerment, strengthen the community social fabric, and support sustainable development. Based on previous studies, Valle del Cauca has suitable soil and climatic conditions for this crop, making it one of the country's most promising regions for its cultivation.